2018
DOI: 10.3390/nu10111567
|View full text |Cite
|
Sign up to set email alerts
|

Ginger Extract Ameliorates Obesity and Inflammation via Regulating MicroRNA-21/132 Expression and AMPK Activation in White Adipose Tissue

Abstract: Ginger is a plant whose rhizome is used as a spice or folk medicine. We aimed to investigate the effect of ginger root extract on obesity and inflammation in rats fed a high-fat diet. Sprague-Dawley rats were divided into three groups and fed either a 45% high-fat diet (HF), HF + hot-water extract of ginger (WEG; 8 g/kg diet), or HF + high-hydrostatic pressure extract of ginger (HPG; 8 g/kg diet) for 10 weeks. The HPG group had lower body weight and white adipose tissue (WAT) mass compared to the HF group. Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 33 publications
2
37
1
1
Order By: Relevance
“…Additionally, 6-gingerol significantly decreased hepatic miR-107-3p level, thereby increasing PPARα and CPT1α genes [303]. Kim et al investigated molecular factors involved in lipid metabolism and inflammation of the white adipose tissue (WAT), including miRNAs, modulated by GEx in Sprague-Dawley rats fed a high-fat diet [304]. They reported that GEx reduced body weight and WAT mass, mRNA levels of adipogenic genes, PPARγ, adipocyte protein 2 (aP2), as well as pro-inflammatory cytokines (TNFα, IL-6 and MCP-1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, 6-gingerol significantly decreased hepatic miR-107-3p level, thereby increasing PPARα and CPT1α genes [303]. Kim et al investigated molecular factors involved in lipid metabolism and inflammation of the white adipose tissue (WAT), including miRNAs, modulated by GEx in Sprague-Dawley rats fed a high-fat diet [304]. They reported that GEx reduced body weight and WAT mass, mRNA levels of adipogenic genes, PPARγ, adipocyte protein 2 (aP2), as well as pro-inflammatory cytokines (TNFα, IL-6 and MCP-1).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this report showed downregulated expression of miR-132 and miR-21 in WAT of rats after GEx administration, in parallel with a greater AMPK activity. The authors assumed that the reduced miR-21 and miR-132 levels could be associated with the post-translational regulation of genes involved in adipogenesis and inflammation in high-fat diet fed rats [304].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mRNA and miR expression levels were analyzed by quantitative real-time PCR (qRT-PCR) as described previously. 19 Total RNA from 3T3 adipocytes was extracted using TRIzol reagent (GeneAll Biotechnology, Seoul, Korea). cDNA for mRNA and miR was synthesized using M-MLV Reverse Transcriptase (Bioneer, Daejeon, Korea) and miRNA cDNA Synthesis kit with Poly (A) Polymerase Tailing (ABM, Inc., Richmond, BC, Canada), respectively.…”
Section: Mrna and Mir Expressionmentioning
confidence: 99%
“…[31][32][33][34][35] We previously found that HHP extract of ginger suppressed miR-21 and miR-132 expression and increased AMPK activation in adipose tissue of obese rats. 19 In addition, Zerumbone, a sesquiterpene isolated from…”
Section: Fig 3 Effects Of Mfe On Gpdh Activity In Adipocytes 3t3-l1mentioning
confidence: 99%